THE USE OF SEMANTIC MAPPING STRATEGY TO FACILITATE STUDENTS’ VOCABULARY DEVELOPMENT IN PRE-WRITING ACTIVITY - Rachmawati, Ismet Laili (Dinamika Pendidikan, 2015)
This study was aimed to examine the effectiveness of semantic mapping strategy to facilitate students’ vocabulary development in pre-writing activity for the seventh graders. Factorial design experiment was used in this study. The participants of this study were the seventh graders of Junior High School 6 of Tegal which consisted of one class as try out group and two classes, each of which was the control and experiment group.  The research questions were analyzed by both pretest and posttest. The results of this study showed that; (1) the slow learners’ vocabulary in pre-writing activity did not significantly develop, (2) semantic mapping facilitated slow learners’ vocabulary development in pre-writing activity by encouraging them to produce as many words as they could, (3) the fast learners’ vocabulary development in pre-writing activity was not satisfying, (4) semantic mapping strategy facilitated fast learners’ vocabulary development in pre-writing activity, (5) all of the slow learners got lower score than fast learners when they were taught by non-semantic map, (6) when they were taught by semantic mapping strategy developed significantly, and (7) semantic mapping strategy has an important role for the students’ learning achievement.